2020
DOI: 10.3389/fmicb.2020.00188
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess for Production, Characteristics, and Biotechnological Applications of Fungal Phytases

Abstract: Phytases are a group of enzymes that hydrolyze the phospho-monoester bonds of phytates. Phytates are one of the major forms of phosphorus found in plant tissues. Fungi are mainly used for phytase production. The production of fungal phytases has been achieved under three different fermentation methods including solid-state, semi-solid-state, and submerged fermentation. Agricultural residues and other waste materials have been used as substrates for the evaluation of enzyme production in the fermentation proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 179 publications
0
32
0
3
Order By: Relevance
“…Notably, SSF conditions are commonly used in enzyme production, particularly cellulase and xylanase [ 22 ]. Furthermore, commercially available exogenous phytases are commonly derived from microorganisms using SSF, SSSF, and SMF [ 34 ]. The major advantage of fungal SSF is that the fungi can grow on complex natural substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SSF conditions are commonly used in enzyme production, particularly cellulase and xylanase [ 22 ]. Furthermore, commercially available exogenous phytases are commonly derived from microorganisms using SSF, SSSF, and SMF [ 34 ]. The major advantage of fungal SSF is that the fungi can grow on complex natural substrates.…”
Section: Discussionmentioning
confidence: 99%
“…This observation agrees with that obtained by Patki et al, 22 where they found that the molecular weight of phytase enzyme produced by bacteria isolated from mangrove soil was in the range of 16-22 KDa. Also, Jatuwong et al 2 reported that phytases produced by fungi are considered as monomeric proteins and possess molecular weights in the range between 14 and 353 kDa. On the other hand, Zhang et al 23 reported that fungal phytase which was extracted from fruiting bodies of the shiitake mushroom (Lentinus edodes), had a monomeric structure with a molecular mass of 14 kDa.…”
Section: Purification and Molecular Weight Determination Of Aspergillmentioning
confidence: 99%
“…1 Phytases (myo-inositol hexakisphosphate phosphohydrolases) are a special class of acid phosphatases that catalyze the hydrolysis of phytate to less phosphorylated myo-inositol derivatives (in some cases to free myoinositol) and releasing of inorganic phosphate. 2 These enzymes act to hydrolyze phytic acid, the main form of the accumulated phosphorus in most of cereal oil seeds, grains, and plants, 1 to release inorganic phosphate. 3 In the last few years, industrial applications of enzymes have increased, where they are used in detergents, pharmaceuticals, food, feed and other products.…”
Section: Introductionmentioning
confidence: 99%
“…Extremozymes possess useful native metabolic functions with potential for application in industrial and biotechnological processes. These include: cellulases (Ueda et al 2010;Li et al 2018), and other carbohydrate-degrading enzymes such as esterases (Charavgi et al 2013), amylases (Agrawal, Dwevedi, and Kayastha 2019;Wu et al 2018), xylanases (Basit et al 2018;Sunna and Bergquist 2003), proteases (Jayakumar et al 2012;Barzkar et al 2018), pectinases (Kaur and Satyanarayana 2004), keratinases (Wu et al 2017;Korniłłowicz-Kowalska and Bohacz 2011), lipases (Schreck and Grunden 2014), peroxidases (Merlino et al 2010) and phytases (Jatuwong et al 2020;Berka et al 1998).…”
Section: Mesophilic Vs Extremophilic Enzymesmentioning
confidence: 99%